Identity Work, Loss and Preferred Identities: A Study of UK Business School Deans. Issue 6 (June 2021) - Brown, Andrew D.; Lewis, Michael A.; Oliver, Nick
This paper investigates how leaders construct 'loss' identity narratives which defuse the scope for external attack and sustain self-meanings. We draw on a sample of 31 United Kingdom business school deans, who although often depicted as multi-talented, high-status achievers, are also targets for criticism and have high rates of turnover. Our study makes two principal contributions. First, we argue that leaders may employ a specific pattern of identity work involving talk about loss to construct identities that bolster their leadership by presenting them as making sacrifices for their institutions. Losses are ubiquitous and malleable discursive resources that constitute both identity threats and opportunities for constructing preferred identities. Second, we deepen understanding of 'preferred identities', i.e. normative self-narratives that specify who people want to be, and to be seen to be, and which serve self-meaning and impression management functions. Preferred identities, though, do not necessarily serve people's interests, and deans tied themselves to demanding requirements by authoring themselves as research credible, scrupulously moral, hard-working professionals.